Analisis Pengaruh Struktur Modal dan Kinerja Keuangan Terhadap Nilai Perusahaan Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Marsalena; Lakoni, Idham; Safrianti, Sintia (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to analyze the effect of the company's capital structure and financial performance on company value in banking companies listed on the IDX for the 2019-2021 period. This study uses associative, namely research that aims to determine the relationship between two or more variables. The samples used in this study were 28 banking companies listed on the IDX for the period 2019 – 2021. To test the existing hypotheses in the study the researchers used two statistical tests, namely the partial test (T test) and the Simultaneous Test (F Test). The data analysis used in this research is descriptive analysis. Based on the results of the t test, the significance value of the DAR, DER, LDAR, LDER, ROA, and ROE variables was <0.05 and the significance value of the NPL variable was > 0.05. Meanwhile, the results of the f test of all independent variables obtained a significance value of F (0.000) <0.05. The results of the study can be concluded that capital structure and financial performance partially and simultaneously have a significant influence on company value in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. This research is expected to be one of the additional references for similar research. For further research, other variables may be used which may affect firm value but have not been discussed in this study.